2016
DOI: 10.1038/mtna.2016.76
|View full text |Cite
|
Sign up to set email alerts
|

The Functionality of Minimal PiggyBac Transposons in Mammalian Cells

Abstract: Minimal piggyBac vectors are a modified single-plasmid version of the classical piggyBac delivery system that can be used for stable transgene integration. These vectors have a truncated terminal domain in the delivery cassette and thus, integrate significantly less flanking transposon DNA into host cell chromatin than classical piggyBac vectors. Herein, we test various characteristics of this modified transposon. The integration efficiency of minimal piggyBac vectors was inversely related to the size of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…Notably, de novo ICR methylation occurred in accordance with the silencing of reprogramming factors. A previous study demonstrated that de novo DNA methylation plays a role in PB silencing (Troyanovsky et al., 2016). It is thus possible that the same machinery is involved in de novo ICR methylation and PB silencing.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, de novo ICR methylation occurred in accordance with the silencing of reprogramming factors. A previous study demonstrated that de novo DNA methylation plays a role in PB silencing (Troyanovsky et al., 2016). It is thus possible that the same machinery is involved in de novo ICR methylation and PB silencing.…”
Section: Discussionmentioning
confidence: 99%
“…A potential improvement to the system is a re-excision deficient piggyBac vector. By moving the majority of the TRE sequence outside of the transposon to the non-inserted backbone of the donor plasmid, the size of the inserted TRE can be reduced with minimal loss of transposition efficiency (52, 53). Once inserted into the genome, the transposon lacks full-length TREs and cannot be efficiently excised.…”
Section: Discussionmentioning
confidence: 99%
“…An all-in-one-type plasmid, called mPB-GLuc-mCherry, which confers simultaneous expression of both mCherry (red fluorescent protein) and GLuc (secretory Gaussia luciferase) together with PB transposase, was injected subcutaneously into the tails of mice followed by in vivo EP locally across the injection site [64]. They observed a GLuc signal six months after gene delivery.…”
Section: Gene Delivery To Tailmentioning
confidence: 99%